Analisis Kebutuhan Drainase Di Desa Senali - Mekar Ria Pangaribuan; Apriadi Apriadi (MAJALAH TEKNIK SIMES, 2022)
Abstract The location of the road in Senali Village, North Bengkulu Regency is a shortcut that does not pass through the city center, if high rainfall results in water flowing through the road, as well as puddles of water around people's homes, this is due to the absence of adequate drainage channels to drain runoff. rain on roads and community sewers. The purpose of this research is to design the dimensions of road drainage in Senali Village by calculating the annual rainfall data. The results of the study showed that the condition of inundation on the Senali Village road and community houses as a result of the absence of good drainage on the road body and due to high rainfall, a drainage design was planned by calculating the intensity of rainfall for the last 15 years (data from the Statistics Agency). the amount of rainfall X1 = 4577 mm, the arithmetic mean of cumulative rain (X) = 305.13 and the standard deviation (Sx) = 77.55 and the value of the amount of rainfall for the return period T years (mm)/24 hours XT is obtained = 370.11 mm. The dimension selection is a trapezoidal model with a size of Q=0, 38 m3/second h = 0,52 m W=0,36 m B=0,53 m and A= 1,05 m.